Initiating a Marketing Mix in The Regulation of The Sale of State-owned Assets - Trisulo, Tri; Budi Susilo (Pandecta Research Law Journal, 2025)
State properties (BMN) that are auctioned do not always sell well at the first opportunity. Failure in the first auction could have an impact on the increasingly uneconomic value of the BMN because the condition can get worse/obsolete. This condition triggers the idea of implementing a marketing mix in regulations so that BMN sales are more optimal. This is legal research, intending to analyze the implementation of the principle "economically more profitable for the country", as well as analyzing the marketing mix as an aspect that can be considered in regulations, especially in the BMN sales process. This study uses a normative juridical method with a conceptual approach. Using primary legal materials and secondary law, processed and analyzed qualitatively, reinforced by the opinions of expert sources. The results of the study found that the 7 aspects of the marketing mix (product, price, place, promotion, people, physical evidence, and process) do not conflict with the principle "economically more profitable for the country". Overall, the marketing mix deserves to be considered in the sale of state-owned goods to be abolished.  Sales of BMN with the application of a marketing mix according to marketing principles are expected to increase the potential for state revenues, and legally be more adaptive to the community.